Single layer and multilayer vacuum-arc coatings based on the nitride TiAlSiYN: composition, structure, properties - Beresnev, V. M.; Sobol, O. V.; Pogrebnyak, A. D.; Lytovchenko, S. V.; Ivanov, O. N.; Nyemchenko, U. S.; Srebniuk, P. А.; Meylekhov, A. A.; Barmin, A. E.; Stolbovoy, V. A.; Novikov, V. Yu.; Mazilin, B. A.; et al. (My University, 2017)
Using high-technological vacuum-arc evaporation in the atmosphere of nitrogen with ion bombardment, single- and multilayer coatings based on TiAlSiYN with high mechanical characteristics were obtained: hardness of the coatings reached 49.5 GPA, resistance to wear, with the value of the critical point LC5 reaching 184.92 N. The peculiarities of radiation-induced effect at applying bias potential Ub were found: formation of nitride coatings based on fcc metallic lattice with the preferred orientation of crystallites with the texture axis [111], as well as simultaneous growth of hardness. Hardness of both single- and multilayer coatings increases by 40-50 % at the increase of Ub from 50 to 200 V. Formation of silicon-containing layers of TiAlSiYN during the deposition contributes to reaching increased hardness, which, in the case of single-layer coating obtained at Ub = -200 V is 49.5 GPA, which corresponds to super hard state. The mechanisms of structure formation, defining the resulting mechanical characteristics of single- and multi-layer coatings based on TiAlSiYN nitride have been discussed.

З використанням високотехнологічного вакуумно-дугового випаровування в атмосфері азоту з іонним бомбардуванням були отримані одношарові і багатошарові покриття на основі TiAlSiYN з високими механічними характеристиками: твердістю, що досягає 49,5 ГПа; стійкістю до зношування з величиною критичної точки LC5, що досягає 184,92 Н. Виявлено особливості радіаційно-стимульованого впливу при подачі потенціалу зміщення Uзм: формування в нітридах покриттів на основі металевих ГЦК-граток переважної орієнтації кристалітів з віссю текстури [111], а також збільшення при цьому твердості. При збільшенні Uзм від 50 до 200 В твердість як одношарових, так і багатошарових покриттів підвищується на 40…50%. Формування при осадженні шарів TiAlSiYN, що містять кремній, сприяє досягненню підвищеної твердості, яка в одношарового покриття, отриманого при Uзм = -200 В, становить 49,5 ГПа, що відповідає надтвердому стану. Обговорено механізми формування структури, що визначає отримані механічні характеристики одношарових і багатошарових покриттів на основі нітриду TiAlSiYN.
Одношарові і багатошарові вакуумно-дугові покриття на основі нітриду TiAlSiYN: склад, структура, властивості